Diesel fuel particulate emission control using low-cost catalytic materials. (15th October 2021) - Khobragade, Rohini; Saravanan, Govindachetty; Einaga, Hisahiro; Nagashima, Hideo; Shukla, Pravesh; Gupta, Tarun; Kumar Agarwal, Avinash; Labhasetwar, Nitin
Graphical abstract: Highlights: Manganese (Mn)-substituted strontium ferrite (SFM) showed enhanced diesel particulate matter (PM) oxidation performance. SFM showed a multi-cycle, stable diesel PM oxidation performance compared with the reference catalysts. Mn-substitution in the lattice of strontium ferrite improves not only its durability but also inhibits agglomeration of catalyst particles. Abstract: Diesel fuel and engine is still projected as a relatively efficient and cleaner in terms of GHG emissions per unit energy generation provided PM emissions are controlled. The catalyst based after-exhaust treatment technologies are very efficient but expensive. Diesel PM oxidation catalysts with matching performance at a lower cost compared to the commercial precious metal catalysts are therefore much required as alternative, due to the vulnerabilities associated with the precious metals in terms of their limited reserves and limited geographical mineral distribution. Low-cost non-precious metal based manganese (Mn)-substituted strontium ferrite (SrFe0.9 Mn0.1 O3-δ ) (SFM) catalysts have been systematically explored, which exhibit improved diesel particulate matter (DPM) catalytic oxidation performance. The available oxygen content in SFM is significantly higher compared to that of pure perovskite phase of strontium ferrite (SrFeO3-δ ) (SFO) due to the Mn-substitution. The onset temperature ( T o ) and maximum conversion temperature ( T m ) of SFM for PM oxidation was observed at 270 and 380 °C, respectively, which is significantly lower than that of SFO ( T o  = 295 °C; T m  = 440 °C). SFM showed multi-cycle, stable diesel PM oxidation performance compared to that of SFO and manganese oxide dispersed SFO. The durability of SFO is improved substantially upon substitution of Mn in its lattice and this catalyst possess potential for practical applications of diesel PM emission reduction.